Memahami perilaku mahasiswa gen z dalam mengelola keuangan pribadi melalui perspektif mental accounting - Anak Agung Istri Pradnyarani Dewi; I Dewa Ayu Eka Pertiwi; Luh Putu Lusi Setyandarini Surya (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
This study examines the financial management behavior of Generation Z students from a mental accounting perspective. Growing up in the digital era, Generation Z has extensive access to digital wallets, Buy Now Pay Later (BNPL) services, and e-commerce platforms. While these technologies offer convenience, they also increase the risk of consumptive behavior and fear of missing out (FOMO). This qualitative study involved eight Generation Z students, both those who earn their own income and those who rely on parental allowances. Data were collected through interviews, observations, and documentation. The analysis was guided by Thaler’s (1999) mental accounting framework, focusing on four dimensions: framing effect, specific accounts and self-control, decision making and evaluation, and the hedonic treadmill. The findings show that students tend to allocate their income into mental categories such as basic needs, entertainment, and savings. These allocations are managed through simple methods, including manual records, separate accounts, or intuitive judgment. Although social media trends and digital promotions often encourage impulsive spending, some students are able to redirect these influences toward productive financial behaviors. Overall, the study highlights the importance of strengthening mental accounting–based financial literacy to support responsible financial management and well-being among Generation Z students.